2011
DOI: 10.1155/2011/892736
|View full text |Cite
|
Sign up to set email alerts
|

Free Vibrations of a Reddy-Bickford Multi-Span Beam Carrying Multiple Spring-Mass Systems

Abstract: Abstract. The structural elements supporting motors or engines are frequently seen in technological applications. The operation of machine may introduce additional dynamic stresses on the beam. It is important, then, to know the natural frequencies of the coupled beam-mass system, in order to obtain a proper design of the structural elements. The literature regarding the free vibration analysis of Bernoulli-Euler and Timoshenko single-span beams carrying a number of spring-mass system and multi-span beams carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Numerous authors have studied the free and/or forced response of beams carrying in-span mass or spring-mass systems. In most investigations on the free vibration, different authors have used analytical methods to determine the exact solutions for the natural frequencies and mode shapes (e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13] and references mentioned therein).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have studied the free and/or forced response of beams carrying in-span mass or spring-mass systems. In most investigations on the free vibration, different authors have used analytical methods to determine the exact solutions for the natural frequencies and mode shapes (e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13] and references mentioned therein).…”
Section: Introductionmentioning
confidence: 99%
“…When investigating the forced vibration of beams, the traditional methods are direct integration method and mode superposition approach. Kim and Dickinson (1988), Yesilce and Demirdag (2008), and Yesilce (2013) studied the forced vibration of beams by mode superposition method. Green’s function is another method to deal with the definite solution problem.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…They concluded that increasing the axial compressive force leads to reduction in natural frequency unlike increasing the relative stiffness and the stiffness ratio which leads to increasing in natural frequency. Yesilce (2011) investigated the free vibration analysis of multi-span beams carrying multiple spring-mass systems based on TSDT. They used the exact solutions for the natural frequencies and mode shapes.…”
Section: Introductionmentioning
confidence: 99%